Caffeine intolerance and the patient’s clinical picture: pharmacokinetics, genetic predisposition, and interactions with psychotropic medications — a narrative review - Psiuk, Arkadiusz Adam; Szymocha, Joanna; Tsukerman, Jarosław; Wojas, Aleksandra (Journal of Education, Health and Sport, 2026)
Background: Caffeine is the most widely consumed psychoactive substance worldwide, yet its intake is rarely quantified in routine psychiatric or cardiological assessment. While IgE-mediated allergy appears exceptional, intolerance and hypersensitivity seem common and may reflect polygenic and metabolic variability that is often clinically underrecognised. Aim: To synthesise current evidence on caffeine pharmacokinetics, on the genetic determinants of inter-individual variability — particularly CYP1A2 and ADORA2A — and on clinically relevant interactions with psychotropic medications. Material and methods: A narrative review was performed using PubMed, Scopus and Google Scholar. Articles published in English addressing pharmacokinetics, pharmacogenomics, psychiatric symptomatology and drug–drug interactions of caffeine were considered. Original studies and reviews were included; case reports were retained when clinically illustrative. Results: Caffeine acts mainly through non-selective antagonism of A1 and A2A adenosine receptors, with downstream modulation of dopaminergic, noradrenergic and HPA-axis signalling. Variants of CYP1A2 (e.g. rs762551) define slow and rapid metabolisers, shaping plasma half-life and accumulation risk. ADORA2A polymorphisms (e.g. rs5751876) may modulate anxiogenic susceptibility independently of hepatic clearance. Co-administration with clozapine or olanzapine may raise plasma drug concentrations and toxicity risk; fluvoxamine, a potent CYP1A2 inhibitor, may extend the caffeine half-life severalfold, producing presentations easily mistaken for akathisia or serotonin syndrome. Conclusions: Caffeine intake — including hidden dietary and over-the-counter sources — should be systematically assessed before initiating psychotropic therapy. Pharmacogenomic profiling may support personalisation in treatment-resistant or atypically responsive patients.